Latin American Experience in Constitutional and Legal Guarantees of Freedom of the Media - Tulnev, Michael A.; Agafonova, Natalya Yu.; Krotov, Andrey V.; Kuksin, Ivan N.; Markhgeym, Marina V. (Cuestiones Políticas, 2020)
The objective of the research was to analyze the Latin American experience in constitutional guarantees regarding freedom of expression in the media. The document summarizes the results of a comparative legal study dedicated to the texts included in the constitutions of the Latin American states regarding the identification of norms that guarantee the freedom of the media in them. It has been established that most of the declared constitutions contain traditional guarantees of media freedom expressed in the legalization of this substantive freedom, its implementation without censorship and restrictions under the threat of responsibility for its abuse. Methodologically, the study was built on the basis of a dialectical approach for the dissemination of legal phenomena and processes using general scientific methods (systemic, logical, analysis and synthesis) and particular. In conclusion, it is evident that it is typical that the constitutions of Latin American states combine freedom of thought, expression and media in a single provision. In all other aspects, the list of identified guarantees is variable and in many countries they have no impact on the concrete reality.